Screening of two native isolates of entomopathogenic nematodes, Heterorhabditis indica and Heterorhabditis bacteriophora, for temperature and moisture stress tolerance: SCREENING OF TWO NATIVE ISOLATES OF ENTOMOPATHOGENIC NEMATODES - GAYATRI BANDARU,; DURAIMURUGAN PONNUSAMY,; SARADA CHUNDURI, (Journal of Oilseeds Research, 2022)
Entomopathogenic nematodes (EPNs) are obligate parasites infecting a wide range ofinsect species and are one of promising biocontrol agents with potential in insect pest management. Temperature and soil moisture play an important role for their sustenance in soil and their efficiency varies greatly under different climatic conditions. The present studywas aimed to study the effect oftemperature and soil moisture on survival, infectivity and reproduction of two EPNs viz., Heterorhabditis indica and H. bacteriophora. The IJs of both the EPNs were exposed to different temperatures and soil moisture levels. Results revealed that survival of both EPNs effected at 5ºC. Survival of H. indica decreased from 54% to 29% after exposure to 5ºC for 48 h. None of the EPNs survived at 35ºC and 40ºC. Infectivity and reproduction potential of both the EPNs tested was highest at 30ºC. No decrease in infectivity was observed with increase in exposure time to different temperatures in both the EPN species. Slight decrease in reproductive potential was observed in H. bacteriophora when exposed to 30ºC for 48h. None of the tested EPNs infected Galleria mellonella larva at 5ºC, 35ºC and 40ºC. Both the EPNs tested showed high infectivity at soil moistures more than 10%. Minimum infection was observed at soil moistures below 10%. Our study revealed that temperature range of 20ºC-30ºC and soil moisture of >10% was found optimum for survival, infectivity and reproduction ofthe testedEPNs. Both the EPNs in this study showed similar temperature and moisture requirements.